Contribution of circulatory cells to asthma exacerbations and lung tissue-resident CD4 T cell memory - Sethi, Gurupreet S.; Gracias, Donald; Croft, Michael (Frontiers in Immunology, 2022)
Tissue-resident memory CD4 T cells (Trm) are thought to be a major contributor to asthma relapse, but the role of circulatory T cells in asthma exacerbations or to maintaining the population of lung Trm cells is not fully understood. Here, we used a house dust mite allergen-based murine model of asthma relapse, and monitored the development of lung effector/Trm phenotype CD44hiCD62LloCD69+ CD4 T cells. To determine the contribution of circulatory cells, mice were treated with FTY720, to block lymphocyte egress from lymph nodes. Inhibiting the primary migration of circulatory cells to the lungs mitigated the accumulation and expansion of allergen-driven Trm phenotype cells, but subsequent allergen challenges still resulted in strong lung inflammation and Trm cell accumulation. This was blocked if FTY720 was also given at the time of allergen re-exposure, showing that new circulatory cells contributed to this lung memory/effector T cell pool at times well after the initial sensitization. However, once lung-localized Trm cells developed at high frequency, circulatory cells were not required to maintain this population following allergen re-encounter, even though circulatory cells still were major contributors to the overall asthmatic lung inflammatory response. Our results suggest that strategies that target the response of circulatory memory T cells and Trm cells together might be required to strongly inhibit T cell reactivity to airborne allergens and to limit exacerbations of asthma and their reoccurrence, but the contribution of circulatory T cells might vary in long-term asthmatics possessing a large stable Trm cell population in the lungs.